PLANEACIÓN ESTRATÉGICA APLICADA A LA COOPERATIVA DE AHORRO Y CRÉDITO “CARIAMANGA” DE LA CIUDAD DE CARIAMANGA, PERIODO 2019-2023 - Pacheco Calva, Andrea Isabel (2019)
In a financial market are external and internal changes that directly or indirectly affect the organizations or financial entities, which seek to establish action plans necessary to enhance their growth, being the most appropriate means the formulation of strategic planning. Based on the above, the following thesis work is proposed, whose general objective is to design a strategic plan applied to the Cooperativa de Ahorro y Crédito “Cariamanga” in the city of Cariamanga, period 2019-2023, in order to provide a clearer vision of what the entity is doing and determine where it wants to go, boosting the well-being of society through motivation to its partners, generating new sources of work and in the same way fulfilling its objectives, policies and strategies. In order to comply with the specific objectives, a diagnosis was made of the current situation of the cooperative through the analysis of its internal factors, through the application of surveys to the administrative staff and members of the cooperative, in addition to conducting a targeted interview. the general manager of the same and the collection of bibliographic information, also the external analysis allowed to obtain information from the economic, political, social, cultural and technological scenarios Subsequently, a vertical (2018), horizontal analysis was developed and financial indicators were applied through the pearl monitoring system to know the economic and financial situation of the cooperative, serving as a complement to the development of the MIF and MEF matrix Next, the CPM Matrix (Competitive Profile Matrix) was developed where the most important competitor for the cooperative is established, after the analysis of the current situation and the strategic analysis the SWOT was developed, which allowed to determine the different strategies that will later be classified and hierarchized through the QSPM Matrix (Quantum Strategic Planning Matrix) 5 Consequently, strategies were designed that will optimize and allow the development and growth of the “Cariamanga” Savings and Credit Cooperative, with the purpose of improving and strengthening it, through the action plan and the elaboration of the AOP (Annual Operating Plan), which is a management instrument to meet the proposed objectives Finally, this thesis provides its contribution as a tool focused on strategic direction and control, linked to the economic and financial development and growth of the COAC "Cariamanga", in order to achieve its financial positioning through proper administrative management and effective